2017
DOI: 10.1016/j.molmet.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cholinergic potentiation of insulin secretion from pancreatic islets by chronic elevation of glucose and fatty acids: Protection by casein kinase 2 inhibitor

Abstract: ObjectivesChronic hyperlipidemia and hyperglycemia are characteristic features of type 2 diabetes (T2DM) that are thought to cause or contribute to β-cell dysfunction by “glucolipotoxicity.” Previously we have shown that acute treatment of pancreatic islets with fatty acids (FA) decreases acetylcholine-potentiated insulin secretion. This acetylcholine response is mediated by M3 muscarinic receptors, which play a key role in regulating β-cell function. Here we examine whether chronic FA exposure also inhibits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Muscarinic receptors are G protein-coupled receptors whose activity may be modulated by targeting downstream receptor kinases. For example, small molecule inhibition of casein kinase 2 (CK2) reduces agonist-induced phosphorylation of ␤-cell M 3 receptors, enhancing acetylcholine-potentiated insulin secretion from mouse and human islets, protecting mice from diet-induced diabetes (18), and protecting both mouse and human islets from lipotoxicity (8). Future studies will need to translate muscarinic signaling-targeted approaches to human models of metabolic disease and patients at risk for and affected by type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic receptors are G protein-coupled receptors whose activity may be modulated by targeting downstream receptor kinases. For example, small molecule inhibition of casein kinase 2 (CK2) reduces agonist-induced phosphorylation of ␤-cell M 3 receptors, enhancing acetylcholine-potentiated insulin secretion from mouse and human islets, protecting mice from diet-induced diabetes (18), and protecting both mouse and human islets from lipotoxicity (8). Future studies will need to translate muscarinic signaling-targeted approaches to human models of metabolic disease and patients at risk for and affected by type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CK2 downregulation seemed to counteract the β-granule phosphoprotein kinesin heavy chain phosphorylation and stimulate the insulin secretion by promoting β-granule transport along microtubules in pancreatic β-cells. 284 …”
Section: Ck2 In Human Diseasesmentioning
confidence: 99%
“…Numerous studies collectively have shown that prolonged (over 24-72 h) incubation of beta cells and islets with a high concentration of FA (0.2-0.5 mM) in the presence of glucose causes apoptosis and reduces insulin secretion (glucolipotoxicity) through activation of multiple stress pathways, including ceramide generation, ER stress, oxidative stress, mitochondrial dysfunction, and inflammation. [79][80][81] While evidence exists for each stress pathway's contribution to lipotoxicity, it remains inconclusive how these relate to the beta cell failure that occurs over decades in humans. Below, we review evidence connecting beta cell dysfunction in humans with the exposure of beta cells to lipids through recent clinical and metabolomic studies, the understanding of lipotoxicity in beta cells, and the gap in knowledge that requires future studies.…”
Section: Lipotoxicity and Lipid Metabolismmentioning
confidence: 99%